The Relationship of Lifelong Learning Competencies with Learning Approaches and Self-Efficacy - Fatma Çetin; Zeynep Demirtaş (Sakarya University Journal of Education)
The study aims to investigate the relationship between the lifelong learning competencies of the students studying in the faculty of education and learning approaches as well as self-efficacy. Lifelong Learning Competence Scale, Learning Approaches Scale, and General Self-Efficacy Scale were used to collect the data for the study. In the study, findings showed that self-management competencies and deep learning among the sub-dimensions of lifelong learning competencies of the students studying in the faculty of education are positively and significantly correlated with strategic learning and self-efficacy, it has been also found that learning-to-learn competency sub-dimension and deep learning, strategic learning, as well as superficial learning, are also positively and significantly correlated; however, no significant relationship was found with self-efficacy. Initiative and entrepreneurship competencies and the sub-dimension of information acquisition competencies were found to be positively correlated with deep learning, strategic learning, and self-efficacy; however, no significant relationship was found with superficial learning. The sub-dimension of digital competencies and the sub-dimension of decisionmaking competence have a significant and positive relationship with deep learning, strategic learning, and self-efficacy however, no significant relationship was found with superficial learning.